A CGE Analysis of the Impacts of a Carbon Tax on Provincial Economy in China. Issue 6 (2nd June 2016) - Zhang, Xingping; Guo, Zhengquan; Zheng, Yuhua; Zhu, Jinchen; Yang, Jing
ABSTRACT: This article conducts a computable general equilibrium (CGE) model to investigate the impacts of a carbon tax on economy at province levels in China since China features significantly differentiated development modes across regions. Three representative provinces including Henan, Fujian, and Chongqing are selected as the sample. The empirical results indicate that carbon tax is an efficient policy to reduce carbon emissions accompanied with negative impact on provincial economy. To cushion the negative impacts of carbon tax, a moderate carbon tax rate and carbon tax recycling policy are recommended according to the simulation results.